THE RELATIONSHIP BETWEEN ECTTOMORPH SKELETAL SHAPE AND INCIDENCE OF ANGLE MALOCCLUSION TO 16 YEARS OLD STUDENTS AT SMAN 4 PADANG - Feby Ramadhani; Fadil Oenzil; Hidayati Hidayati (Andalas Dental Journal, 2015)
Malocclusion is a deviation of normal occlusion in the growth process of the teeth caused by certain factors. Angle malocclusion is one of the existing malocclusion classifications by looking at the shape of the first molar relationship. One of the causes of malocclusion is the lack of nutrition. Adequate nutrition canbe seen from the shape of a person's skeletal, according to Sheldon classification it is divided into three, namely, ectomorph (skinny), mesomorphk (normal) and endomorph (fat). This study was conducted to determine the relationship between ectomorph skeletal shape and the incidence of Angle malocclusion to SMA Negeri 4 Padang students. The study was conducted with comparative cross-sectional design. The samples were divided into two groups: the ectomorph skeletal shape (thin) and mesomorph skeletal shape (normal), the number of respondents respectively 28. Group of skeletal shape was determined by using BMI (Body Mass Index) and direct malocclusion examination in the respondents’mouth using mouth glass by looking at the respondent first molar relationship in accordance with the concept of Angle malocclusion classification. Of the results on ectomorph and mesomorph respondents with the incidence of malocclusion, it is not found a significant relationship with the use of chi-square analysis (p>0.05). Conclusion of the study show that there is no relationship between ectomorph skeletal shape and Angle malocclusion. Ectomorph and mesomorph skeletal shape and do not have significant differences. Key words :malocclusion, BMI, skeletal shape